Self-calibration stress luminescent material caused by phase separation as well as preparation and application of self-calibration stress luminescent material

By using Ca2-xB2O5:Mnx material, high-temperature solid-phase method and proportional self-calibration scheme, the problem of large errors in existing stress luminescent materials under environmental uncertainty is solved, and stress visualization with high reliability and portability is achieved.

CN119709188AActive Publication Date: 2025-03-28ZHENGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311278791.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Existing stress-emitting materials are prone to severe errors under environmental uncertainty and require pre-excitation, resulting in inconvenience.

Method used

Ca2-xB2O5:Mnx is used as a ratio-type self-calibrated stress luminescent material caused by phase separation, and is prepared by high-temperature solid phase method. A proportional self-calibration scheme is used to reduce environmental interference and improve reliability.

Benefits of technology

High-reliability stress visualization under different environmental conditions is achieved. The material does not require pre-ultraviolet light and has strong stress emission under mechanical action. Color changes can be used for visual sensing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709188A_ABST
    Figure CN119709188A_ABST
Patent Text Reader

Abstract

The invention provides a self-calibration stress luminescent material caused by phase separation as well as preparation and application thereof, the stress luminescent material takes Ca2-xB2O5 as a matrix, Mnx as an activator, 0.16 lt; xlt; and 0.22, preparing the stress luminescent material Ca (2-x) B2O5: Mnx. The stress luminescent material prepared by the invention is sintered and synthesized in air by adopting a high-temperature solid-phase method, is low in cost and environment-friendly, and does not generate harmful substances in the preparation process; pre-irradiation is not needed, strong stress luminescence is achieved under the mechanical effect, and direct observation can be achieved through naked eyes in the dark environment; and environmental interference is reduced through a proportional self-calibration scheme, stress visualization of absolute strength is replaced, and the reliability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of stress luminescent materials, and particularly relates to a self-calibrating stress luminescent material caused by phase separation, a preparation method thereof, and an application thereof. Background Art

[0002] Stress luminescence refers to the phenomenon that solid materials release photons under the action of mechanical forces, including impacts, squeezes, frictions, stretches, ultrasounds, etc. In recent years, with the research of people, stress luminescent materials have shown great application potential in the fields of stress sensing, stress visualization, structural damage monitoring, information storage, security anti-counterfeiting, etc.

[0003] Some optical sensors based on fluorescence intensity require pre-excitation, such as ultraviolet lamp irradiation or incandescent lamp irradiation, so they are not portable, and they are easily affected by errors caused by changes in signal acquisition efficiency. The uncertainty of the environment will inevitably amplify this influence, resulting in serious errors in optical sensing. In fact, this negative influence can be reduced by a proportional self-calibration scheme, instead of an absolute intensity-based scheme, to obtain better reliability. The previous stress visualization can be qualitatively analyzed, while the ratio-type self-calibrating stress visualization can achieve quantitative analysis. At the same time, the proportional self-calibration scheme usually causes a change in luminescence color, which is beneficial to visual sensing. Therefore, it is particularly important to develop a ratio-type self-calibrating stress visualization material in this field. Summary of the Invention

[0004] The present invention provides a ratio-type self-calibrating stress visualization material caused by phase separation, a preparation method thereof, and an application thereof. Using Ca 2-x B2O5 as a matrix and Mn x (0.16 < x < 0.22) as an activator, a stress luminescent material Ca 2-x B2O5:Mn x is prepared. It is sintered in air, with low cost, environmental friendliness, and no harmful substances generated during the preparation process.

[0005] The technical solution of the present invention is realized as follows: A self-calibrating stress luminescent material caused by phase separation, wherein the stress luminescent material is Ca 2-x B2O5:Mn x , 0.16 < x < 0.22.

[0006] Furthermore, 0.17 ≤ x ≤ 0.21.

[0007] The self-calibrating stress luminescent material caused by phase separation is prepared from raw materials with the following mole fractions: 50% of H3BO3, 49.6% - 49.7% of CaO, and 0.3% - 0.4% of MnCO3.

[0008] The self-calibrated stress luminescent material caused by phase separation is prepared from the following raw materials in molar fractions: 50% H3BO3, 49.6%-49.7% CaO and 0.325%-0.375% MnCO3.

[0009] The method for preparing the stress luminescent material comprises the following steps:

[0010] Grind and mix H3BO3, CaO and MnCO3 to obtain a mixture;

[0011] The mixture was sintered at 750-850 °C in air for 6 h and ground to obtain the ratiometric self-calibrated stress luminescent material Ca2+ induced by phase separation. 2-x B2O5:Mn x , 0.16 <x<0.22。

[0012] Furthermore, the mixture is sintered by heating to 300°C at 20°C / min, then heating to 750-850°C at 10°C / min and sintering for 6h, then cooling to 200°C at 20°C / min, and finally cooling naturally to room temperature.

[0013] The ratio-type self-calibrated stress luminescent film caused by phase separation is prepared from the stress luminescent material and PDMS colloid.

[0014] Furthermore, the preparation method of the stress luminescent film is as follows: the stress luminescent material and the PDMS colloid are evenly mixed to obtain a mixed liquid, the mixed liquid is evenly coated in the mold, and the colloid is heated and cured after sealing and coating to obtain a ratio-type self-calibrated stress luminescent film caused by phase separation.

[0015] Furthermore, in the mixed liquid, the mass percentage of the stress luminescent material is 30%-40%.

[0016] Furthermore, the heating curing temperature is 80° C. and the curing time is 0.5 h-2 h.

[0017] Ca 2-x B2O5:Mn x Application as a phase separation-induced ratiometric self-aligned stress luminescent material, 0.16 <x<0.22。

[0018] Ca 2-x B2O5:Mn x Application of stress luminescent materials as ratiometric self-calibration induced by phase separation in stress visualization, 0.16 <x<0.22。

[0019] Beneficial effects of the present invention:

[0020] The present invention uses Ca 2-x B2O5 is the matrix, Mnx (0.16 < x < 0.22) is used as an activator to prepare the stress luminescent material Ca 2- x B2O5:Mn x For the preparation method of the stress luminescent material of the present invention, the high-temperature solid-phase method is adopted. The preparation process is simple, the sintering temperature is low, and it can be sintered in air, and the conditions are easy to control; no toxic gas is generated during the preparation process, and there is no pollution to the environment; the interference of the environment is reduced through the proportional self-calibration scheme, and the stress visualization of the absolute intensity is achieved, improving the reliability.

[0021] Ca of the present invention 2-x B2O5:Mn x As a stress luminescent material for ratio-type self-calibration caused by phase separation, no prior ultraviolet light irradiation is required. After mixing and curing Ca 2-x B2O5:Mn x with PDMS colloid, the prepared stress luminescent film shows ratio-type self-calibration stress luminescence within the elastic limit of the material, has strong stress luminescence under mechanical actions (such as stretching, friction, etc.), can be directly observed by the naked eye in a dark environment, and its stress luminescence color is different under different stresses, having very wide application value in the field of visual sensing. Brief Description of the Drawings

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0023] Figure 1 is the XRD pattern of the stress luminescent material Ca 2-x B2O5:Mn x ;

[0024] Figure 2 is the photoluminescence pattern of Ca2B2O5: 0.35% Mn prepared in Example 1;

[0025] Figure 3 is the stress luminescence pattern of the stress luminescent material Ca2B2O5: 0.35% Mn prepared in Example 1;

[0026] Figure 4 is the stress luminescence photograph of the stress luminescent material Ca2B2O5: 0.35% Mn prepared in Example 1;

[0027] Figure 5CIE diagram of the stress luminescent material Ca2B2O5: 0.35% Mn prepared in Example 1;

[0028] Figure 6 CIE diagram of Ca2B2O5: 0.325% Mn prepared in Example 4;

[0029] Figure 7 CIE diagram of Ca2B2O5: 0.375% Mn prepared in Example 5;

[0030] Figure 8 CIE diagram of the stress luminescent material Ca2B2O5: 0.3% Mn prepared in Example 3;

[0031] Fig. 9 CIE diagram of the stress luminescent material Ca2B2O5: 0.4% Mn prepared in Example 2. Detailed implementation manners

[0032] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.

[0033] Select H3BO3, CaO, and MnCO3 as raw materials, and weigh the corresponding elements of H3BO3, CaO, and MnCO3 according to the composition and ratio; grind and mix the H3BO3, CaO, and MnCO3 raw materials by ball milling to obtain a mixture; sinter the mixture in air at 750 - 850 °C for 6 h, and then grind to obtain the ratio-type self-calibrated stress luminescent material Ca 2-x B2O5:Mn x (0.16 < x < 0.22); uniformly mix the ratio-type self-calibrated stress luminescent material with PDMS colloid to obtain a mixed liquid, uniformly coat the mixed liquid in a polytetrafluoroethylene mold, wrap it with plastic wrap, and heat to cure the colloid to obtain a ratio-type self-calibrated stress luminescent film caused by phase separation.

[0034] The following will be described in detail with specific examples.

[0035] Example 1

[0036] Taking Ca 1.8077 B2O5:Mn 0.1923 as an example, a preparation method of a self-calibrated stress luminescent material caused by phase separation includes the following steps:

[0037] (1) grinding and mixing H3BO3 with a purity of 99.8wt%, CaO and MnCO3 to obtain a mixed powder; based on the mole fraction of the mixed powder being 100%, the mixed powder comprises 50% of H3BO3, 49.65% of CaO and 0.35% of MnCO3;

[0038] (2) The mixed powder of step (1) was placed in air at a temperature of 800° C. and sintered for 6 h, and then ground to obtain a ratio-type self-calibrated stress luminescent material Ca2+ induced by phase separation. 1.8077 B2O5:Mn 0.1923 .

[0039] Step (2) Ca 1.8077 B2O5:Mn 0.1923 The stress luminescent material and PDMS colloid were mixed evenly to obtain a mixed liquid, which was evenly coated in the mold, wrapped with plastic wrap, and heated and cured at 80°C for 30 minutes to obtain Ca 1.8077 B2O5:Mn 0.1923 (Abbreviated as Ca2B2O5:0.35%Mn) stress luminescent film.

[0040] Example 2

[0041] Ca 1.7802 B2O5:Mn 0.2198 For example, a method for preparing a self-calibrated stress luminescent material caused by phase separation comprises the following steps:

[0042] (1) grinding and mixing high-purity H3BO3, CaO and MnCO3 to obtain a mixed powder; based on the mole fraction of the mixed powder being 100%, the mixed powder comprises 50% of H3BO3, 49.6% of CaO and 0.4% of MnCO3;

[0043] (2) The mixed powder of step (1) was placed in air at a temperature of 800°C and sintered for 6 hours, and then ground to obtain Ca 1.7802 B2O5:Mn 0.2198 A phase-separation-induced ratiometric self-aligned stress-luminescent material.

[0044] Step (2) Ca 1.7802 B2O5:Mn 0.2198 The stress luminescent material and PDMS colloid were mixed evenly to obtain a mixed liquid, which was evenly coated in the mold, wrapped with plastic wrap, and heated and cured at 80°C for 30 minutes to obtain Ca 1.7802 B2O5:Mn 0.2198 (Abbreviated as Ca2B2O5:0.4%Mn) stress luminescent film.

[0045] Example 3

[0046] Ca 1.8352 B2O5:Mn 0.1648 For example, a method for preparing a self-calibrated stress luminescent material caused by phase separation comprises the following steps:

[0047] (1) grinding and mixing high-purity H3BO3, CaO and MnCO3 to obtain a mixed powder; based on the mole fraction of the mixed powder being 100%, the mixed powder comprises 50% of H3BO3, 49.7% of CaO and 0.3% of MnCO3;

[0048] (2) The mixed powder of step (1) was placed in air at a temperature of 800° C. and sintered for 6 h, and then ground to obtain a ratio-type self-calibrated stress luminescent material Ca2+ induced by phase separation. 1.8352 B2O5:Mn 0.1648 .

[0049] Step (2) Ca 1.8352 B2O5:Mn 0.1648 The stress luminescent material and PDMS colloid were mixed evenly to obtain a mixed liquid, which was evenly coated in the mold, wrapped with plastic wrap, and heated and cured at 80°C for 30 minutes to obtain Ca 1.8352 B2O5:Mn 0.1648 (Abbreviated as Ca2B2O5:0.3%Mn) stress luminescent film.

[0050] Example 4

[0051] Ca 1.8215 B2O5:Mn 0.17858 For example, a method for preparing a self-calibrated stress luminescent material caused by phase separation comprises the following steps:

[0052] (1) grinding and mixing high-purity H3BO3, CaO and MnCO3 to obtain a mixed powder; taking the mole fraction of the mixed powder as 100%, the mixed powder comprises 50% of H3BO3, 49.675% of CaO and 0.325% of MnCO3;

[0053] (2) The mixed powder of step (1) was placed in air at a temperature of 800° C. and sintered for 6 h, and then ground to obtain a ratio-type self-calibrated stress luminescent material Ca2+ induced by phase separation. 1.8215 B2O5:Mn 0.17858 .

[0054] Step (2) Ca 1.8215 B2O5:Mn 0.17858 The stress luminescent material and PDMS colloid were mixed evenly to obtain a mixed liquid, which was evenly coated in the mold, wrapped with plastic wrap, and heated and cured at 80°C for 30 minutes to obtain Ca 1.8215B2O5:Mn 0.17858 (Abbreviated as Ca2B2O5:0.325%Mn) stress luminescent film.

[0055] Example 5

[0056] Ca 1.7940 B2O5:Mn 0.2060 For example, a method for preparing a self-calibrated stress luminescent material caused by phase separation comprises the following steps:

[0057] (1) grinding and mixing high-purity H3BO3, CaO and MnCO3 to obtain a mixed powder; taking the mole fraction of the mixed powder as 100%, the mixed powder comprises 50% of H3BO3, 49.625% of CaO and 0.375% of MnCO3;

[0058] (2) The mixed powder of step (1) was placed in air at a temperature of 800° C. and sintered for 6 h, and then ground to obtain a ratio-type self-calibrated stress luminescent material Ca2+ induced by phase separation. 1.7940 B2O5:Mn 0.2060 .

[0059] Step (2) Ca 1.7940 B2O5:Mn 0.2060 The stress luminescent material and PDMS colloid were mixed evenly to obtain a mixed liquid, which was evenly coated in the mold, wrapped with plastic wrap, and heated and cured at 80°C for 30 minutes to obtain Ca 1.7940 B2O5:Mn 0.2060 (Abbreviated as Ca2B2O5:0.375%Mn) stress luminescent film.

[0060] Comparative Example 1

[0061] Ca 1.9451 B2O5:Mn 0.0549 For example, a method for preparing a self-calibrated stress luminescent material caused by phase separation comprises the following steps:

[0062] (1) grinding and mixing high-purity H3BO3, CaO and MnCO3 to obtain a mixed powder; based on the mole fraction of the mixed powder being 100%, the mixed powder comprises 50% of H3BO3, 49.9% of CaO and 0.1% of MnCO3;

[0063] (2) The mixed powder of step (1) was placed in air at a temperature of 800° C. and sintered for 6 h, and then ground to obtain a ratio-type self-calibrated stress luminescent material Ca2+ induced by phase separation. 1.9451 B2O5:Mn 0.0549 .

[0064] Step (2) Ca1.9451 B2O5:Mn 0.0549 The stress luminescent material and PDMS colloid were mixed evenly to obtain a mixed liquid, which was evenly coated in the mold, wrapped with plastic wrap, and heated and cured at 80°C for 30 minutes to obtain Ca 1.9451 B2O5:Mn 0.0549 Stress luminescent coating.

[0065] Comparative Example 2

[0066] Ca 1.4506 B2O5:Mn 0.5494 For example, a method for preparing a self-calibrated stress luminescent material caused by phase separation comprises the following steps:

[0067] (1) grinding and mixing high-purity H3BO3, CaO and MnCO3 to obtain a mixed powder; taking the mole fraction of the mixed powder as 100%, the mixed powder comprises 50% of H3BO3, 49% of CaO and 1% of MnCO3;

[0068] (2) The mixed powder of step (1) was placed in air at a temperature of 800°C and sintered for 6 hours, and then ground to obtain Ca 1.4506 B2O5:Mn 0.5494 A phase-separation-induced ratiometric self-aligned stress-luminescent material.

[0069] Step (2) Ca 1.4506 B2O5:Mn 0.5494 The stress luminescent material and PDMS colloid were mixed evenly to obtain a mixed liquid, which was evenly coated in the mold, wrapped with plastic wrap, and heated and cured at 80°C for 30 minutes to obtain Ca 1.4506 B2O5:Mn 0.5494 Stress luminescent coating.

[0070] Comparative Example 3

[0071] This comparative example is basically the same as Example 1, except that: 1.8901 B2O5:Mn 0.10998 For example, H3BO3 accounts for 50%, CaO accounts for 49.8% and MnCO3 accounts for 0.2% in the mixed material.

[0072] Comparative Example 4

[0073] This comparative example is basically the same as Example 1, except that: 1.5605 B2O5:Mn 0.4395 For example, H3BO3 accounts for 50%, CaO accounts for 49.2% and MnCO3 accounts for 0.8% in the mixed material.

[0074] The mass ratio of the stress luminescent material prepared in Examples 1-5 and Comparative Examples 1-4 to the PDMS colloid is about 1:2, the mass ratio of PDMS to the curing agent in the PDMS colloid is 10:1, and the length and width of the mold coating layer are 3 cm and 0.5 cm respectively, and the thickness is 0.5 mm.

[0075] Figure 1 The stress luminescent material Ca prepared in Examples 1-5 and Comparative Examples 1-4 2-x B2O5:Mn x XRD pattern of . Figure 1 The XRD matches well with the PDF standard card (JCDP#22-0139), but with the change of Mn doping concentration, the XRD changes and the peaks in the standard card (JCDP#32-0155) appear. Phase separation will occur when the MnCO3 mole fraction is in the range of 0.3% to 0.4%, and Mn will show phase separation in a certain concentration range.

[0076] Figure 2 The photoluminescence graph of the stress luminescent material Ca2B2O5:0.35%Mn prepared in Example 1 shows two luminescence centers under different excitation wavelengths, and the double peaks change with the change of the excitation wavelength, showing excitation dependence.

[0077] Figure 3 This is the stress luminescence image of the stress luminescence material Ca2B2O5:0.35%Mn prepared in Example 1. When the linear motor is used for the tensile test, Figure 4 It can be seen that the stress luminescence intensity of Ca2B2O5:0.35%Mn increases with the strain from 40% to 100%. The stress luminescence intensity of Ca2B2O5:0.35%Mn is about 500.

[0078] Figure 4 These are stress luminescence photographs of the stress luminescence material Ca2B2O5:0.35%Mn prepared in Example 1 under different strains. As the strain increases, the color of the stress luminescence changes from yellow-green to orange-yellow.

[0079] Figure 5 This is the CIE diagram of the stress luminescent material Ca2B2O5:0.35%Mn prepared in Example 1. The change in the stress luminescent color can also be seen from the CIE diagram. As the strain increases, the stress luminescent color changes from yellow-green to orange-yellow.

[0080] Figure 6 This is the CIE diagram of the stress luminescent material Ca2B2O5:0.325%Mn prepared in Example 4. The change in the stress luminescent color can also be seen from the CIE diagram.

[0081] Figure 7 This is the CIE diagram of the stress luminescent material Ca2B2O5:0.375%Mn prepared in Example 5. The change in the stress luminescent color can also be seen from the CIE diagram.

[0082] Figure 8 This is the CIE diagram of the stress luminescent material Ca2B2O5:0.3%Mn prepared in Example 3. It can also be seen from the CIE diagram that its stress luminescent color changes slightly with strain.

[0083] Fig. 9 This is the CIE diagram of the stress luminescent material Ca2B2O5:0.4%Mn prepared in Example 2. It can also be seen from the CIE diagram that its stress luminescent color changes slightly with strain.

[0084] Depend on Figure 5-7 It can be seen that the stress luminescence colors of the stress luminescence materials Ca2B2O5: 0.325%Mn and Ca2B2O5: 0.375%Mn will change with the increase of strain, but the degree of change is not as obvious as that of the stress luminescence material Ca2B2O5: 0.35%Mn.

[0085] The above tests confirm that phase separation can make its stress luminescence color different under different strains, realizing ratiometric self-calibrated stress visualization.

[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A phase separation-induced self-calibrated stress luminescent material, characterized in that: The stress luminescent material is Ca 2- x B2O5:Mn x , 0.16 <x<0.22。 2. The phase separation-induced self-aligned stress luminescent material according to claim 1, characterized in that: 0.17≤x≤0.21。 3. A phase separation-induced self-aligned stress luminescent material according to claim 1 or 2, characterized in that: Prepared from the following raw materials in mole fractions: 50% H3BO3, 49.6%-49.7% CaO and 0.3%-0.4% MnCO3.

4. The self-aligned stress luminescent material caused by phase separation according to claim 1 or 2, characterized in that: Prepared from the following raw materials in mole fractions: 50% H3BO3, 49.6%-49.7% CaO and 0.325%-0.375% MnCO3.

5. The method for preparing the self-aligned stress luminescent material caused by phase separation according to any one of claims 1 to 4, characterized in that: The following steps are involved: Grind and mix H3BO3, CaO and MnCO3 to obtain a mixture; The mixture was sintered at 750-850 °C in air for 6 h and ground to obtain the ratiometric self-calibrated stress luminescent material Ca 2-x B2O5:Mn x , 0.16 <x<0.22。 6. The preparation method according to claim 5, characterized in that: The mixture was sintered by heating to 300°C at 20°C / min, then heating to 750-850°C at 10°C / min and sintering for 6h, then cooling to 200°C at 20°C / min, and finally cooling naturally to room temperature.

7. A self-calibrated stress luminescent film, characterized in that: The invention is prepared from the stress luminescent material according to claim 1 or 2 and PDMS colloid. 8.Ca 2-x B2O5:Mn x Application as a phase separation induced self-aligned stress luminescent material, 0.16 <x<0.22。 9.Ca 2-x B2O5:Mn x Application of self-calibrated stress luminescent materials induced by phase separation in stress visualization, 0.16 <x<0.22。

Citation Information

Patent Citations

  • Phosphors and phosphor-converted LEDS

    CN107406765A

  • Stress luminescent material, stress luminescent coating and preparation method thereof

    CN115746835A